Web-Based Student Learning Activities and Development Information System Using Pieces Analysis at OSI Tutoring Center - Septiani, Anugrah; Heni Rahmawati; Luthfi Nur Azizah (Jurnal Ilmiah Informatika dan Komputer, 2025)
Tutoring (BIMBEL) is a form of non-formal education that plays a role in improving students' academic achievements. Oemah Sinau Indonesia (OSI) in Banjarnegara still uses Excel and physical reports to record learning activities and student development, making the process of searching and distributing data less efficient. This study aims to build a web-based information system for learning activities and student development using the PIECES analysis as a system evaluation method at OSI tutoring. The system development uses the Waterfall method with PHP programming language, Laravel framework, and data storage based on Firebase Realtime Database. System testing is conducted using Black-box testing to ensure the system functions according to user needs, and all 10 test scenarios were successfully executed with a "successful" status. System feasibility evaluation uses PIECES analysis (Performance, Information, Economy, Control, Efficiency, Service) was conducted through the distribution of questionnaires to 11 respondents consisting of admins, mentors, and student guardians. The evaluation results showed an average feasibility score of 95%, categorized as very feasible. Specifically, the Performance and Efficiency aspects received the highest scores of 97%, indicating an improvement in the speed and ease of administrative processes as well as real-time access to information. Based on the testing and analysis results, this system is considered effective in replacing manual record-keeping, improving data accuracy, strengthening access control, and facilitating communication between the tutoring center and student guardians. Thus, this information system is proven feasible to be used as a solution for digitalizing learning administration at OSI.